Co-existence of Follicular Lymphoma in the Lymph Node with High-grade B Cell Lymphoma in the Bone Marrow of a Patient with Spontaneous Tumor Lysis Syndrome - Giatra, Chara; Sykaras, Alexandros G.; Constantinou, Fotis; Gennimata, Victoria; Sampaziotis, Dimitrios; Geladari, Eleni; Kounatidis, Dimitris; Vallianou, Natalia G. (Cardiovascular & Haematological Disorders - Drug Targets, 2020)
A significant percentage of B-cell lymphomas are characterized by bone marrow involvement (BMI) at diagnosis. In most cases, there is a concordance between the type of lymphoma present in the lymph node and the lymphoma present in the bone marrow. Herein, we presented a sixty-seven years old female patient, who was diagnosed with High-Grade B-cell Lymphoma (HGBL) in the bone marrow, while simultaneously, in the peripheral lymph node, the presence of Follicular Lymphoma (FL) was noted. The patient was presented to the hospital with spontaneous tumor lysis syndrome, a finding compatible with the aggressive course of the HGBL. To our knowledge, this is the first case of the co-existence of HGBL in the bone marrow and FL in a lymph node, which might be attributed to merely a coincidence or to the transformation of the cells in the preferable milieu of the bone marrow.
Keywords: follicular lymphoma FL